Defining transnationalism - Clavin, P (2005)
This article offers an introduction to the essays in the theme issue, an overview of the reasons behind the recent resurgence of interest in transnationalist phenomena and a consideration of what the term means. Its places the topic in the different fields of international, world, regional, local and national history. The essay argues that transnationalism is best understood not as fostering bounded networks, but as creating honeycombs, a structure that sustains and gives shapes to the identities of nation-states, international and local institutions, and particular social and geographic spaces. A honeycomb binds, but it also contains hollowed-out spaces where organisations, individuals and ideas can wither away to be replaced by new groups, people and innovations. © 2005 Cambridge University Press.